2001
DOI: 10.1007/s004670000538
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen years experience in pediatric acute dialysis: analysis of predictors of outcome

Abstract: This study reviewed the 18-year experience of acute dialysis in the pediatric intensive care unit, in order to identify factors that could predict outcome, and to determine whether newer modalities of acute dialysis have influenced this outcome. Sixty-six children (ages 1 day to 19 years) received acute dialysis from May 1980 to April 1998. Factors predicting outcome were analyzed using univariate and Cox regression analysis. Modality of dialysis in the first 15 years was exclusively peritoneal dialysis. with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 19 publications
2
27
6
Order By: Relevance
“…Several risk factors, not always consistently, had been defined for mortality in previous series: younger age [3,26], older age [21], extrarenal diseases [3,22,[26][27][28][29][30][31][32][33], sepsis, septic shock, multiorgan failure [3,26,29,31,[34][35][36][37][38][39], oligoanuria and/or anuria [22,29,40,41], hypotension [32,34,37], use of pressor drugs [33], need for MV [22,26,32,35,36,40], need for dialysis [22,32,35,39,40], and fluid overload [19,42,43]. A common major weaknesses to all of these studies were the relatively small size of the patient groups, the lack of a uniform definition of AKI, staging, and standardized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors, not always consistently, had been defined for mortality in previous series: younger age [3,26], older age [21], extrarenal diseases [3,22,[26][27][28][29][30][31][32][33], sepsis, septic shock, multiorgan failure [3,26,29,31,[34][35][36][37][38][39], oligoanuria and/or anuria [22,29,40,41], hypotension [32,34,37], use of pressor drugs [33], need for MV [22,26,32,35,36,40], need for dialysis [22,32,35,39,40], and fluid overload [19,42,43]. A common major weaknesses to all of these studies were the relatively small size of the patient groups, the lack of a uniform definition of AKI, staging, and standardized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As in the present study, Gong et al reported CVVHDF as the primary initial treatment modality in paediatric patients with ARF [6].…”
Section: Discussionmentioning
confidence: 66%
“…These observations suggest less severe diseases in the second decade. The need for vasopressors is associated with a high mortality [2], as well as low MAP [6,18,19] and ventilatory support [6]. In contrast, all infants younger than one year had low MAP and all needed ventilatory and vasopressor support in the second decade [2,6,18,19].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations